2014
DOI: 10.3788/lop51.061401
|View full text |Cite
|
Sign up to set email alerts
|

Study on Balling Phenomena in Selective Laser Melting

Abstract: Balling phenomena is a common defect in selective laser melting (SLM) process, it is the main reason causing high surface roughness、pores、tilt delamination and other defects, seriously affect the density and mechanical properties of parts. The classification and formation process of balls、 influencing factors and hazards of balling phenomena at home and abroad are summarized systematacially. Results show that different metal balls have different formation mechanisms. The formation process of balling phenomena … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The SLM process consists of complicated physics, such as absorption and transmission of laser energy [16], rapid melting and solidification of material, microstructure evolution [17,18], flow in a molten pool [19], and materials evaporation [20]. The process is thus affected by the aforementioned factors to form defects of porosities, incomplete fusion holes, cracks, and impurities, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The SLM process consists of complicated physics, such as absorption and transmission of laser energy [16], rapid melting and solidification of material, microstructure evolution [17,18], flow in a molten pool [19], and materials evaporation [20]. The process is thus affected by the aforementioned factors to form defects of porosities, incomplete fusion holes, cracks, and impurities, etc.…”
Section: Introductionmentioning
confidence: 99%
“…SLM production sample quality is influenced by many factors, for instance, laser scanning speed, powder and shape, energy input, and so on. The SLM production process involves complex physical processes, such as fast melting and solidification [ 67 , 68 ], absorption and transmission of laser energy [ 69 ], as well as material flow in the molten pool [ 70 ].…”
Section: Advanced Additive Manufacturing Techniquesmentioning
confidence: 99%
“…[15][16][17][18] Among the few studies, Li et al 19 suggested that the reason for the spheroidization problem is a wetting problem between the liquid metal and the solid surface but did not indicate whether this was related to the oxygen content. Zhang et al, 20 when studying the SLM spheroidization problem, found that the size of the metal balls in the melt pool was related to the oxygen content and that the size of the metal balls in the melt pool increased with increasing the oxygen content. Kruth et al 21,22 found that the spheroidization phenomenon was inextricably linked to surface oxidation and that the formation of spheroidization was inseparable from surface oxidation, and also that the generated oxide lm could be broken with a higher energy laser or by adding a deoxidizer to the liquid metal to stop the occurrence of spheroidization.…”
Section: Introductionmentioning
confidence: 99%